The Influence of Organizational Learning, Innovation Culture, and Dynamic Capabilities on the Business Strategic Agility of Digital-Based MSMEs - Winarno, Basuki; Masbullah; Sugiarti; Feni Marnilin; Pande Gde Bagus Naya Primananda; Adi Soeprapto (Journal of Innovative and Creativity, 2026)
The research investigates the impact of Organizational Learning and Innovation Culture and Dynamic Capabilities on Business Strategic Agility within digital-based MSMEs. The researchers conducted a quantitative study which involved distributing questionnaires to 180 selected digital MSME owners and managers through purposive sampling. The study required respondents to meet three criteria which included running a business for two years and using digital platforms and participating in business decision-making. The researchers used multiple linear regression analysis to analyze the data. The researchers conducted validity and reliability tests and classical assumption tests which included testing normality and testing for heteroscedasticity and multicollinearity. The study established that Organizational Learning and Innovation Culture and Dynamic Capabilities lead to Business Strategic Agility in both complete and partial forms. The research results indicate that digital MSMEs can enhance their strategic agility through improved organizational learning practices and development of innovation culture and dynamic business capabilities. The study will enhance strategic management literature while providing digital MSME development resources which support Indonesian digital business advancement.